Enzymatic Interesterification of Rambutan Kernel Olein and Stearin for Specialty Fats Production - Ramli, Nazaruddin (2008)
In this study, olein and stearin of rambutan kernel fat was produced by fractionation at 15ºC. Purification of crude rambutan fat was also carried out. Fat modification was further developed to generate specialty fat through both fractions of rambutan fat. Besides that, palm mid (PMF), palm olein (POo) and palm stearin IV=34 (POs) were also used in the blending studies. Enzymatic interesterification (EIE) was used in fat modification using lipase TL IM with specific position at 1,3. Among the physico-chemical analyses carried out were solid fat content solid (SFC), melting and crystallization behaviour, free fatty acid (FFA), fatty acid methyl ester composition (FAME), slip melting point (SMP), triacylglyceride (TAG), iodine value (IV) and peroxide value (PV). These characteristics were compared with those of noninteresterification mixture. The interesterified products showed an increase in SMP values ranging from 17 ºC-19.5ºC to 37 ºC-38.5ºC. Interesterified blend had lower SFC at 0 ºC to 20ºC but higher SFC from 25ºC to 37.5ºC when compared to non-EIE products. All interesterified blends were in solid form at room temperature and had ~0 % SFC at 37.5 ºC. All non-EIE blends were in liquid form at room temperature and gave 0% SFC at 35ºC. EIE blends produced significantly higher FFA (17-27 %) than non-EIE blends with only 2-5% FFA. High value of FFA showed that EIE of RKS: PMF:POo with Thermomyces lanuginosa lipase caused a high degree of TAG loss due to increased in rate of hydrolysis. Statistical analysis showed that there was no significant difference (p>0.05) for peroxide value and iodine value between non-EIE blends and EIE blends. Thermal analysis showed that enzymatic interesterification of RKS:PMF:POo had decreased the entalpy of melting and crisytallization of the blends. An optimization study for enzymatic interesterification (EIE) of rambutan kernel stearin (RKFs), palm mid fraction (PMF, IV=34), and palm olein (POo) blends was carried out by Response Surface Method (RSM) to obtain desired blended products. Enzyme load (1.95%- 12.05%), reaction time (1.20-29.80 h), and temperature (16ºC-83ºC) were important determining factors affecting EIE. Based on SFC profile, ratio that has been chosen for optimization study was 30% of RKFs, 32.5% of PMF and 37.5% of POo. The optimal conditions of variables which produced the desired properties for use as margarine was at 47.82ºC with 6.30% an enzyme dosage for 12 h of reaction. Fat blends that were produced at optimal parameters had been used to produce margarine. Margarine that was produced had SFC value of 21.80 % at 10ºC and 19.40% at 20ºC. These profiles indicated that the product has good spreadability effect at refrigerating temperatures and resistance to oil exudation at room temperature. Beside that, margarine that was produced in this study had a good microstructure similar to commercial margarine. Cocoa butter substitute (CBS) was produced through enzymatic interesterification (EIE) of palm stearin (POs), palm mid fraction (PMF) and rambutan kernel olein (RKOo) by using Lipozyme TL IM (Thermomyces lanuginous). Generally, the percentage of SFC and SMP was reduced after EIE process. The percentage of SFC at 37.5oC for sample B (20%POs: 60% PMF: 20%RKOo) and D (20% POs: 50% PMF: 30% RKOo) after EIE process were the lowest SFC (4.51% and 0.51%, respectively). The SMP for sample B was decreased from 47.5ºC to 36.5ºC while sample D was decreased from 50ºC to 34ºC. Free fatty acid and peroxide value for sample B and D were increased after EIE while the fatty acid composition and iodine value did not show any difference after EIE. The DSC thermogram of sample D showed small peak and sharp peak at 10.92ºC and 36.20oC which were similar to cocoa butter profile. Therefore, sample D was chosen to undergo optimization process using Response Surface Method (RSM). Finally, the optimize reaction parameters to produce good CBS was at 50ºC for 4 h with 4.39% of Lipozyme TL IM